DONGENG DALAM PENGAJARAN BAHASA INGGRIS TERHADAP ANAK SEKOLAH DASAR - Siregar, fitri rayani (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2013)
AbstractThis article described Using Sory Telling in Teaching English Toward Elementry School . The story telling can grows and improve a moral intelligences. Using story telling in teaching learning process in English is the one of the way to build the intelligence and one of study media. They can develop their imagination and it can exercises them to solving problem and think well. Through the story telling thestudents can insrease the vocabulary in language developing and it has goal for improve the listening and for comprehend in lestening process. Beside that, for creating enjoy and fun situation. More than anything else when teacher can succeed adaptation and modify adapted for the Ianguage based on the level growth of student Ianguage and storey level difficulty of their English. aaaaaaafinally ,The children is pushed to give an active participation in responding the tales being told, since at the positive responses is expected to reflect the moral intelligences and it is very effective more than suggestion.Key word: Story Telling,Teaching English and Students